Middelalderens bibliotek på Trondenes - Bergesen, Rognald Heiseldal (Novus forlag, 2013)
Preserved medieval books from the stone church at Trondenes in northern norway are investigated to illuminate distinct features of a book collection from the church. In particular, they testify to the use of early printed books (incunabula) in the late Middle Ages in norway. The discussion relates to chronology and the functions of the church. The functions considered are connected to liturgy, canon law, collecting the tithe and the education of priests. Trondenes was an important church consisting of several priests in the late Middle Ages, and the place had been central ever since the Viking age. The presence of an obituary book and an antiphonal may signify a college consisting of many priests at Trondenes as early as the thirteenth century. The local canon law must have been a necessary tool dealing with management of the economic resources in the district. Several preserved library books from Trondenes indicate that the place was an important centre of knowledge in the sixteenth century.